Assessment of gingival thickness in multi‐ethnic subjects with different gingival pigmentation levels. (23rd September 2022) - Nik‐Azis, Nik‐Madihah; Razali, Masfueh; Goh, Victor; Ahmad Shuhaimi, Nurul Nadia; Mohd Nazrin, Nur Aqilah Syuhada
Abstract: Aim: Assessment of the thickness of gingival tissues using the probe visibility test is regarded as the method of choice during routine examinations. However, the probe visibility test has not been validated for patients with gingival pigmentation and its accuracy in populations with physiological gingival pigmentation is yet unknown. This study aims to evaluate different methods for the clinical assessment of gingival thickness in participants with varying levels of gingival pigmentation. Materials and Methods: Buccal mucosa of the maxillary right central incisor teeth of 171 participants was evaluated using four methods, which were direct measurements using calliper, transgingival probing method using an endodontic probe, and probe visibility method using Colorvue biotype probe (CBP) and UNC‐15 probe. The pigmentation of the gingiva was assessed using the Dummett–Gupta oral pigmentation lesion index. Results: The average gingival thickness of the selected population was 1.22 ± 0.38 mm with a distribution of 70% thick and 30% thin gingiva. Transgingival and calliper methods showed good agreement and significant correlation ( r  = 0.229; p  = .003). Visual assessment using CBP and UNC‐15 probe showed poor agreement with the direct measurement methods. Gingival pigmentation significantly affected the probe visibility assessment, reducing the visibility of both the CBP (odds ratio [OR] = 4.00; 95% confidence interval [CI], 1.83–8.74) and UNC‐15 probe (OR = 1.84; 95% CI, 1.05–3.23) while controlling for thickness of the gingiva. Conclusion: The probe visibility method using either CBP or the UNC‐15 probe is affected by the degree of gingival pigmentation. Direct measurements using either a calliper or transgingival probing are recommended as methods to measure the gingival thickness in populations with gingival pigmentation.